Pengembangan Prototipe Sistem Informasi Geografis Fasilitas Olahraga Berbasis Mobile (Studi Kasus Fasilitas Olahraga Di Kecamatan Purwakarta) - Egi Maulana Yusuf; Ismi Kaniawulan (RJOCS (Riau Journal of Computer Science), 2015)
Mobile GIS applications Sports facilities are applications that are used to provide information to users about the info locations of existing sports facilities in the district of Purwakarta along the course route. This application is a mobile application technology based Location Based Service (LBS) that is built on the Android platform, using the Eclipse IDE and Google APIs in development. In search of the user's position, this application utilizes GlobalPositioning System (GPS) which has been integrated with the handset. Map and Driving Route is a major facility that is applied with the help of Google Maps API. Database sports facilities location info taken using secondary data where the data is taken from various sources. Data stored is thelocation of sports facilities.